GAMBARAN HbA1c PASIEN DIABETES MELITUS TIPE 2 DENGAN KOMPLIKASI ULKUS KAKI DIABETIK DI POLIKLINIK PENYAKIT DALAM RSUP SANGLAH DENPASAR PERIODE APRIL-SEPTEMBER 2014 - I Made Dwikayana; A A Ngurah Subawa; I W P Sutirta Yasa (E-Jurnal Medika Udayana, 2016)
Uncontrolled diabetes mellitus type 2 causes complication of diabetic foot ulcers. HbA1c can be used as a parameter DM because of a strong correlation with blood glucose. This study determines the characteristic HbA1c in type 2 diabetes mellitus patient with complications of diabetic foot ulcer at Internal Medicine Policlinic Sanglah Hospital from April to September 2014 based on age, sex, body weight, blood glucose level 2 hours post prandial, and the degree of foot ulcers. This study was an observational with cross sectional descriptive study and sample were taken by total sampling. The data obtained from secondary data from medical record of patients. The results showed 32 samples from most of the patients are between 55-59 years of age with bad HbA1c status as many as 6 people. Based on sex, men with bad HbA1c status as many as 12 people. Patients with normal weight with bad HbA1c status as many as 10 people. Patients with blood glucose control 2 hours post prandial bad with bad HbA1c status as many as 18 people. Patient with stage I of diabetic foot ulcers with bad HbA1c status as many as 9 people and stage IV with bad HbA1c status as many as 8 people. It can be concluded that the control of diabetes based on HbA1c overview of each variable tends to lead to bad control of diabetes mellitus. This results are expected to be the basis for further research to seek treatment and prevention of complications diabetes mellitus more effectively.